Strategies to Prevent Employee Turnover: Implementation Program Employee Engagement & Employee Retention - Susanto, Primadi Candra; Kamsariaty, Kamsariaty; Murdiono, Jatmiko; Nuraeni, Nuraeni; Perwitasari, Erni Pratiwi (Dinasti Publisher, 2024)
The purpose of this scientific article is to provide qualitative insights and descriptions that the variables related to employee engagement, employee turnover and employee retention are important for organizations to be used as a foundation, as well as for other interests. Qualitative research methods can provide valuable insights in analyzing employee engagement, employee retention, and employee turnover. A qualitative approach is focused on understanding an individual's experiences, perceptions, and behaviors and can help uncover the reasons and motivations behind them. One approach in qualitative research in this context can be done through in-depth interviews with employees to explore their perceptions of the factors that affect employee engagement, employee retention, and employee turnover, the strategies implemented must be holistic, involve various dimensions of human resource management, and be directed to create a work environment that motivates and supports career development and overall employee well-being.